Some Anatomical Variations of the Coronary Circulation among Sri Lankan Adults - , S. R. Hulathduwa (Archives of Current Research International, 2021)
The coronary circulation has been the centre of focus of many anatomists, pathologists, cardiologists, cardiothoracic surgeons, physiologists and even the general public especially since the introduction of coronary angiography during the 1960's. Though a large number of data regarding the coronary circulation of the Western populations are available, research about coronary circulation of the Sri Lankan population is comparatively rare. This study comprises of data from 150 autopsy specimens of adult Sri Lankans died due to non-cardiac causes. 99.3% had a tricuspid aortic valve while only in 0.7% the aortic valve was bi-cuspid. The incidence of the ectopic origin of the left and the right coronary artery was equal (1.3%), and the posterior sinus was devoid of coronary ostia. A 55.3% of the study population had a single coronary artery ostium for each main coronary artery. The corresponding figure for the left coronary artery was 91.3%. Six percent (06%) of the right coronary ostia were positioned significantly above the sinus while the corresponding figure for the left coronary ostia was higher (17.5%). The average left ventricular wall thickness for males and females were 13mm and 12mm respectively. Significant muscular bridging (in relation to at-least one coronary artery) was found in 19.3% of the study population. The study concludes that variations in the cardiac anatomy are commoner than expected. As per Kitzman chart, cardiac dimensions of the Sri Lankans are somewhat smaller compared to the dimensions of the Western populations.